2013
DOI: 10.1002/ejlt.201200273
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on the esterification of free fatty acids in jatropha oil

Abstract: Kinetic studies have been carried out on the esterification of free fatty acids (FFAs) in jatropha oil with methanol in the presence of sulphuric acid catalyst at 5 and 10 wt% concentrations relative to free fatty acids (0.4–0.8 wt% relative to oil) and methanol–FFA mole ratios ranging from 20:1 to 80:1. It has been found that a 60:1 methanol–FFA mole ratio and 5 wt% catalyst at 60°C and 500 rpm or above provided a final acid value lower than 1 mg KOH/g oil within 60 min. A kinetic model has been proposed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The results found in the literature also seem to disagree about whether the reaction is exothermic or endothermic. Thus, in some works it was found that the esterification reaction of fatty acids was endothermic, with a very low reaction heat (between 7 and 20 kJ/mol) [27,29,30,44,45], whereas there is apparently only one work that reports an exothermic esterification reaction, with a reaction heat of -11.1 kJ/mol [9].…”
Section: Effect Of Temperature On the Equilibrium And Kineticsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results found in the literature also seem to disagree about whether the reaction is exothermic or endothermic. Thus, in some works it was found that the esterification reaction of fatty acids was endothermic, with a very low reaction heat (between 7 and 20 kJ/mol) [27,29,30,44,45], whereas there is apparently only one work that reports an exothermic esterification reaction, with a reaction heat of -11.1 kJ/mol [9].…”
Section: Effect Of Temperature On the Equilibrium And Kineticsmentioning
confidence: 99%
“…Several authors have investigated the kinetics of the esterification of short chain carboxylic acids [38,46,47] and of the esterification of fatty acids contained in the oils for the production of biodiesel [9,29,32,44].…”
Section: Kinetic Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Freedman et al (1986), Noureddini and Zhu (1997) and Darnoko and Cheryan (2007) have proposed diverse mathematical models for describing batch transesterification processes; Kamarudin et al (1998), Sendzikiene et al (2004), Zheng et al (2006), Berrios et al (2007), Aranda et al (2008), Rani et al (2013) and Vinjamur (2013, 2014) have obtained noteworthy results concerning the mathematical description of the batch esterification processes. The transesterification and esterification processes conducted within batch reactors show flexibility in deployment and relatively high yields; however, it is well-known that the batch processes could increase their production level and can be performed still more efficiently when they are developed within a continuous stirred tank reactor (CSTR) (Levenspiel, 1999).…”
Section: Introductionmentioning
confidence: 99%